Optimasi Penempatan Relay Node Pada Wireless Sensor Networks Menggunakan Algoritme Particle Swarm Optimization (PSO) - Abdul Aziz Hadyansyah Widada; Kasyful Amron; Fariz Andri Bakhtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Precision agriculture is predicted to become the future of the agricultural industry. The application of information technology to enhanced production automation or land security requires that agricultural areas be filled with sensing devices. In fact, many sensors that have been deployed on land cannot send data optimally. The battery lifetime of wireless sensing devices causes network connectivity to be less and affects the final results of land monitoring. Relay node placement in wireless sensor networks field presents a power-limiting solution by dividing the role of data actuators and as hops that forward data towards internet gateway. However, the application of two-tier communication architecture using relay requires a high cost, so that the relay placement needs to be optimized. The research was conducted aimed at optimizing the placement of relays on agricultural land, by proposing optimization strategies that are adapted to conditions in the field. PSO (Particle Swarm Optimization) algorithm is used as a relay placement optimization heuristic method. The results of relay placement optimization show that a collection of relays that are optimized in number and position can produce maximum connectivity value compared to its placement deterministically. The complexity of the method will increase 19-35 percent as the number of relays is considered.